2016
DOI: 10.1080/07053436.2016.1198592
|View full text |Cite
|
Sign up to set email alerts
|

Role of leisure-generated meanings in adaptation to acculturation stress of Korean immigrants in Canada

Abstract: This study tests the hypothesis that leisure-generated meanings would buffer acculturation stress on the psychological and sociocultural adaptation of Korean immigrants (n = 120) in a western Canadian city. Analyses of survey data show that acculturation stress is significantly associated with lower life satisfaction and self-esteem, poorer mental health, and sociocultural adaptation. The study only supports the main effects of leisure-generated meanings on life satisfaction and self-esteem (as indicators of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…It is also common to focus on leisure as experiences characterized by the subjective sense of freedom, involvement, or intrinsic values such as enjoyment or meaning (Mannell & Kleiber, 1997 ; Neulinger, 1981 ). It is debated to what extent these Western conceptualizations reflect meanings and definitions of leisure within diverse cultural contexts of perspectives (Kim & Iwasaki, 2016 ). Thus, it is important to explore subjective experiences and meanings of leisure to guard against imposition of culturally-bound definitions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also common to focus on leisure as experiences characterized by the subjective sense of freedom, involvement, or intrinsic values such as enjoyment or meaning (Mannell & Kleiber, 1997 ; Neulinger, 1981 ). It is debated to what extent these Western conceptualizations reflect meanings and definitions of leisure within diverse cultural contexts of perspectives (Kim & Iwasaki, 2016 ). Thus, it is important to explore subjective experiences and meanings of leisure to guard against imposition of culturally-bound definitions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hurly ( 2019 ) also proposed that leisure can have “ameliorative effects” (p. 3) on newcomers’ lives, particularly due to its potential to reduce stress related to migration (Höglhammer et al, 2015 ). Indeed, experiencing personal, social, or cultural connectedness through leisure can help newcomers overcome acculturative stress or immigration-related challenges which can, in turn, promote health and well-being (Kim & Iwasaki, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some research has revealed distinctions in this relationship that invite a review of this field of study. For example, it has been found that an increase in self-esteem is associated with the practice of leisure activities that are significant for the person or activities where social support from others is perceived [8][9][10][11], while the practice of sedentary activities or activities whose difficulty causes stress is associated with a loss of self-esteem [12][13][14]. Furthermore, self-esteem is seen to be nourished by both leisure and non-leisure, to the point that work is more important than leisure for some people [15,16].…”
Section: Introductionmentioning
confidence: 99%